Molecular mechanisms of Porphyromonas gingivalis-host cell interaction on periodontal diseases - Masaaki Nakayama; Naoya Ohara (Elsevier, 2017)
Porphyromonas gingivalis (P. gingivalis) is a major oral pathogen and associated with periodontal diseases including periodontitis and alveolar bone loss. In this review, we indicate that two virulence factors, which are hemoglobin receptor protein (HbR) and cysteine proteases "gingipains", expressed by P. gingivalis have novel functions on the pathogenicity of P. gingivalis. P. gingivalis produces three types of gingipains and concomitantly several adhesin domains. Among the adhesin domains, hemoglobin receptor protein (HbR), also called HGP15, has the function of induction of interleukin-8 (IL-8) expression in human gingival epithelial cells, indicating the possibility that HbR is associated with P. gingivalis-induced periodontal inflammation. On bacteria-host cells contact, P. gingivalis induces cellular signaling alteration in host cells. Phosphatidylinositol 3-kinase (PI3K) and Akt are well known to play a pivotal role in various cellular physiological functions including cell survival and glucose metabolism in mammalian cells. Recently, we demonstrated that gingipains attenuate the activity of PI3K and Akt, which might have a causal influence on periodontal diseases by chronic infection to the host cells from the speculation of molecular analysis. In this review, we discuss new molecular and biological characterization of the virulence factors from P. gingivalis.